Scientific evidence on access to health services by LGBTQI+ population: Scope review (Research, Society and Development, 2022)
The relationship between users and health services is essential to strengthening the quality of care. The LGBTI+ population, which is composed of populations that are defined by the diversity of gender identity and expression, sexual orientation, and biological sex, suffers prejudice and discrimination in accessing and using these services. This study aimed to identify the scientific evidence in the LGBTQI+ population, to give visibility to the adversities related to the access and use of health services. Scope review carried out at the bases: CINAHL, EBSCOhost, EMBASE; Latindex; LILACS, MEDLINE, Science Direct, SciELO, SCOPUS, Web of Science, with an open period. Original articles with full text available online in English, Spanish or Portuguese were included, with data from Brazil as the object of study. The search resulted in 1,332 potentially eligible articles and, additionally, 4 more articles from references of articles selected in the research, totaling 1336 articles. Of these, 22 met all inclusion criteria. Evidence has shown that the LGBTQI+ population suffers discrimination in healthcare environments and, as a rule, barriers to access. Stigma, discrimination, and cultural and social norms that give preference to heterosexuality, cisgenderism, and endosexism are some of the causes that contribute to these health inequalities. The results of this study show gaps in cultural competencies concerning health, lack of awareness and knowledge of the unique health needs of the LGBTQI+ population, along with non-inclusive attitudes, were identified as possible contributing factors among health professionals and managers.